Repellent effects of Makal, Trichosanthes palmata seed and leaf extracts against Tribolium castaneum (Herbst) and Tribolium confusum Duval (University Journal of Zoology, Rajshahi University, 2007)
Key words: Trichosanthes palmata; repellency; Tribolium castaneum; Tribolium confusum Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 31-34